Wong's essentials of pediatric nursing - Hockenberry, Marilyn J.; Wilson, David , 1950 August 25-; Wong, Donna L. , 1948-2008 (Elsevier/Mosby, 2013)
Provides a foundation in child development and health promotion, and covers specific health problems - organized by age groups and body systems, so you can individualize care at the appropriate level for each child.